Reproducing experiential meaning in translation: A systemic functional linguistics analysis on translating ancient Chinese poetry and prose in political texts - Liu, Qiannan; Li, Xiaolong (Frontiers in Psychology, 2022)
Ancient Chinese poetry and prose (ACPP) are the essence of traditional Chinese culture and also literary gems of the world. Despite the long tradition of previous Chinese Presidents using ACPP in their political addresses, the translation work on the three volumes of Xi Jinping: The Governance of China with much ACPP still poses a daunting challenge to the translation of literary texts in non-literary texts. As experiential meaning is inherent in all kinds of texts, literature, and non-literature, this study, drawing on the sights of Halliday's experiential mode of meaning and register theory in Systemic Functional Linguistics (SFL), explored how the ACPP's experiential meaning was rendered in the political texts, and factors motivating transitivity patterns and shift tendencies. Statistics showed that the translations tend to reproduce the experiential meaning such that it involves more representations of the flow of events and the creation of relationships among entities, focusing more on construing the experience of the physical world rather than personal emotions, feelings, or cognition. Besides, the target text is also inclined to simplify the experiential meaning by compressing and omitting unnecessary transitivity processes and the participant and circumstance nominalization. This research found that the factors responsible for such tendencies include the features of political texts, language differences, the distribution of process types, the delicacy of the transitivity system, and register variations of fields of activity. With these findings, the study is expected to contribute to the SFL approach of studying literary translation in non-literary texts through the prism of experiential meaning and offer guidance in the translation of political literature with ACPP.